Cryo-Electron Microscopy and Biochemical Analysis Offer Insights Into the Effects of Acidic pH, Such as Occur During Acidosis, on the Complement Binding Properties of C-Reactive Protein - Noone, Dylan P.; van der Velden, Tijn T.; Sharp, Thomas H. (Frontiers in Immunology, 2021)
The pentraxin family of proteins includes C-reactive protein (CRP), a canonical marker for the acute phase inflammatory response. As compared to normal physiological conditions in human serum, under conditions associated with damage and inflammation, such as acidosis and the oxidative burst, CRP exhibits modulated biochemical properties that may have a structural basis. Here, we explore how pH and ligand binding affect the structure and biochemical properties of CRP. Cryo-electron microscopy was used to solve structures of CRP at pH 7.5 or pH 5 and in the presence or absence of the ligand phosphocholine (PCh), which yielded 7 new high-resolution structures of CRP, including pentameric and decameric complexes. Structures previously derived from crystallography were imperfect pentagons, as shown by the variable angles between each subunit, whereas pentameric CRP derived from cryoEM was found to have C5 symmetry, with subunits forming a regular pentagon with equal angles. This discrepancy indicates flexibility at the interfaces of monomers that may relate to activation of the complement system by the C1 complex. CRP also appears to readily decamerise in solution into dimers of pentamers, which obscures the postulated binding sites for C1. Subtle structural rearrangements were observed between the conditions tested, including a putative change in histidine protonation that may prime the disulphide bridges for reduction and enhanced ability to activate the immune system. Enzyme-linked immunosorbent assays showed that CRP had markedly increased association to the C1 complex and immunoglobulins under conditions associated with acidosis, whilst a reduction in the Ca2+ concentration lowered this pH-sensitivity for C1q, but not immunoglobulins, suggesting different modes of binding. These data suggest a model whereby a change in the ionic nature of CRP and immunological proteins can make it more adhesive to potential ligands without large structural rearrangements.